Comparison of 4 Laryngoscopes in 2 Difficult Airway Scenarios: A Randomized Crossover Simulation-Based Study. Issue 5 (October 2016) - Altun, Demet; Ozkan-Seyhan, Tulay; Orhan-Sungur, Mukadder; Sivrikoz, Nukhet; Camci, Emre
Abstract : Introduction: The performance of laryngoscopes that have been developed for difficult airways can vary widely. The aim of the study was to compare Macintosh, McCoy, McGrath MAC, and C-MAC laryngoscopes in cervical immobilization and tongue edema scenarios in a mannequin, primarily to evaluate the time to intubation. Methods: In this randomized crossover study, 41 anesthesiology residents used 4 laryngoscopes in a mannequin (SimMan 3G) in 2 different scenarios. Intubation time (insertion of the blade between the teeth, to placement of the endotracheal tube into the trachea) longer than 120 seconds or inability to successfully place the endotracheal tube into the trachea after 5 or more attempts was defined as intubation failure. Besides intubation time, laryngoscopic view, number of intubation attempts, presence of esophageal intubation, need for stylet, difficulty of intubation, and success rate were recorded as secondary outcomes. Results: Intubation time was observed from longest to shortest as McGrath > McCoy > C-MAC > Macintosh in both scenarios. Laryngeal view was better with C-MAC laryngoscope. McGrath laryngoscope performed poorly specifically in tongue edema scenarios, which resulted in higher number of intubation attempts, esophageal intubation, need for intubation stylets, and overall intubation failure. Conclusions: The short intubation time observed with the Macintosh underlines the necessity of familiarity in success. Tongue edema is a more challenging scenario for simulated difficult airway and the McGrath may not be a good choice for such a scenario.